CONCEPT-PROCESS MODEL OF THE 2009 SECONDARY EDUCATION CURRICULUM: ITS EFFECTS ON MATHEMATICS PERFORMANCE - Emerzen L. Echavez (European Scientific Journal, ESJ, 2014)
Education authorities have been finding ways and means in treating the steady decline in the level of competencies of Filipino students in the global market. They have come up with a proposal in changing the 2003 RBEC curriculum to 2009 Secondary Education Curriculum in which the Concept-Process Model will be used as a method of teaching. This study examines the effectiveness of the Concept-Process Model of the 2009 Secondary Education Curriculum on the mathematics performance of the First Year students of Cebu City National Science High School. It made use of the quasi-experimental design in which two groups of respondents were given pre-tests, intervention, and then post-tests of the first and second grading periods of the first year coverage. Results showed that both the control and experimental group showed a significant mean gain in the mathematics performance level of the students. However, results also showed that there was no significant difference between the control and the experimental group in terms of the post-test mathematics level of performance. It further showed that there was no significant mean gain difference between the control and experimental group. In conclusion, the Concept-Process Model of the 2009 SEC was effective in increasing the level of performance of the students in mathematics. It can also be said further that the CPM of the 2009 SEC was as effective as the 2003 RBEC. However, it is recommended that this method must be tested to other concepts of mathematics in the other levels for purpose of reliability and validity. This method may also be tested to other subjects more specifically to the sciences as an alternative method in teaching the concepts of the subject.